Teacher Monitoring Application in Teaching Based on CodeIgniter Framework in High Schools - Syahri Susanto; Bayu Priyatna (Information System; Universitas Buana Perjuangan Karawang, 2020)
This is Teacher monitoring in teaching at one Karawang Middle School, is needed to monitor teachers in teaching in class so it can be seen whether the teacher often does teaching and learning activities or not, teachers do not always attend school then carry out teaching and learning activities and also not teachers are not in attendance does not give assignments as a substitute for learning. This monitoring application can support the teacher monitoring process in teaching in the classroom. The system development method used is a waterfall and uses PHP and MySQL. This application is a consideration of how often the teacher teaches in class.